The total synthesis of 5-methoxy-3,4-dehydroxanthomegnin, dehydroherbarin lactone and 6-ferrocenyl-3,4-dihydroisochromene - Sumani, Jimmy Yaphet Ephet (My University, 2018)
Pyranonaphthoquinones, especially those with lactone functionality, are a class of naturally occurring compounds that exhibit a wide range of biological properties. For example, studies have shown that 10-hydroxy-5,7-dimethoxy-3-methyl-1H-naphtho-[2,3-c]-pyran-1,6,9-trione has a plethora of biological activities which includes, among others, cytotoxicity against McCoy cell lines and significant antibacterial property against Helicobacter pylori. This PhD project describes the total synthesis of 7,9-dimethoxy-3-methyl-1Hbenzo[g]isochromene-1,5,10-trione from simple starting materials in 14 steps in an overall percentage yield of 5%. The synthesis was achieved by subjecting the commercially available, 2,4-dimethoxybenzaldehyde, to a number of synthetic transformation protocols we have developed in our laboratory group. The key steps in the synthesis included the PIFA mediated methoxylation of the naphthalene nucleus that was constructed from the Stobbe condensation reaction and the palladium assisted Wacker oxidation reaction of the naphthoic acid intermediates. We also successfully synthesized 10-hydroxy-5,7-dimethoxy-3-methyl-1Hbenzo[g]isochromene-1,6,9-trione starting from 2,4,5-trimethoxybenzaldehyde in 15 steps in an overall percentage yield of 1%. This was achieved by employing the protocol we established during the synthesis of 7,9-dimethoxy-3-methyl-1H-benzo[g]isochromene-1,5,10trione. In the course of achieving the total syntheses of 7,9-dimethoxy-3-methyl-1Hbenzo[g]isochromene-1,5,10-trione and 10-hydroxy-5,7-dimethoxy-3-methyl-1Hbenzo[g]isochromene-1,6,9-trione a number of unexpected products were isolated and characterized. The second part of the project was aimed at developing a methodology for coupling a ferrocene moiety to 3,4-dihydroisochromene and subjecting the resultant ferrocenyl 3,4dihydroisochromene to oxidative demethylation protocols. Ferrocene coupled hybrid compounds are currently receiving a lot of attention because of their application in medicine. Abstract iii For example, ferroquine is active against both chloroquine-sensitive and chloroquine-resistant Plasmodium falciparum strains. The synthesis of 6-ferrocenyl-(±)-trans-3,4-dihydro-5,8-dimethoxy-1,3-dimethyl-6-vinyl-1Hisochromene was achieved starting from 2,5-dihydroxyacetophenone in 10 steps in an overall percentage yield of 10%. The key steps in this methodology involved the base mediated ring closing reaction which delivered (±)-trans-3,4-dihydro-5,8-dimethoxy-1,3-dimethyl-6-[(E)-1propenyl]-1H-isochromene and the McMurray cross-coupling metathesis reaction which afforded 6-ferrocenyl-(±)-trans-3,4-dihydro-5,8-dimethoxy-1,3-dimethyl-6-vinyl-1Hisochromene. The oxidative demethylation of 6-ferrocenyl-(±)-trans-3,4-dihydro-5,8-dimethoxy-1,3dimethyl-6-vinyl-1H-isochromene to complete the total synthesis of 6-ferrocenyl-(±)-trans3,4-dihydro-1,3-dimethyl-6-vinyl-1H-isochromene-5,8-dione was unsuccessful and an alternative protocol was developed which was aimed at coupling of ferrocene moiety to (±)trans-6-bromo-3,4-dihydro-1,3-dimethyl-1H-isochromene-5,8-dione at the last step. This methodology did not yield the target molecule, 6-ferrocenyl-(±)-trans-3,4-dihydro-1,3dimethyl-6-vinyl-1H-isochromene-5,8-dione. However, a number of potentially biologically important serendipitously obtained compounds were isolated. The last part of this PhD project involved in vitro biological screening of 3 selected compounds synthesized in this project against the Gambian FCR-3 strain of Plasmodium falciparum. All the 3 compounds namely, (±)-trans-15-bromo-5,13-dimethoxy-2,4,10,12tetramethyl-4,7,9,10,12,13-hexahydro-1H-7,13-methanopyrano[4',3':6,7]oxocino[2,3-f]isochromen-8(2H)-one, 3-(chloromethyl)-3,4-dihydro-5,7,10-trimethoxybenzo[g]isochromene1,6,9-trione and bis[(±)-trans-3,4-dihydro-8-methoxy-1,3-dimethyl-1H-isochromen-5yloxy]methane showed promising activity. (±)-Trans-15-bromo-5,13-dimethoxy-2,4,10,12tetramethyl-4,7,9,10,12,13-hexahydro-1H-7,13-methanopyrano[4',3':6,7]oxocino[2,3-f]isochromen-8(2H)-one showed the best activity with an IC50 value of 0.0018 µM. This value was better than the activity shown by the reference compounds, quinine and dihydroartemisinin, which showed activity of 2.81 µM and 0.0061 µM, respectively, under the same assay conditions.
A thesis submitted to the Faculty of Science University of the Witwatersrand Johannesburg in fulfilment of the requirements for the Degree of Doctor of Philosophy, 2018
Keywords: Plasmodium falciparum; Drug resistance